(untitled) (Homoeopathy for All, 2022)
Hypercholesterolemia is a condition characterized by very high levels of cholesterol in the blood. Cholesterol is a waxy, fat like substance that is produced in the body and obtained from foods that come from animals (particularly egg yolks, meat, poultry, fish, and dairy products). The body needs this substance to build cell membranes, make certain hormones and produce compounds that aid in fat digestion. Too much cholesterol, however, increases a person’s risk of developing heart diseases.